Pengaruh Triangle Marketing terhadap Keputusan Nasabah Memilih Tabungan iB Hijrah di PT Bank Muamalat Indonesia KCP Rancaekek - Sari Tilawati Jariah; Faisal Rakhman (Jurnal Dimamu, 2023)
Based on the results of observations, the background of this research is the fluctuation in the number of iB Hijrah Savings customers and how the bank's solution to retain iB Hijrah Savings customers. This study aims to determine how the influence of Internal Marketing, External Marketing, and Interactive Marketing partially and simultaneously on the decision to become iB Hijrah Savings customers at Bank Muamalat Indonesia Rancaekek Branch Office (KCP).. The type of research is quantitative associative with primary data types and uses data collection techniques in the form of observation, interviews, questionnaires and literature studies. The population of this study amounted to 254 respondents with the determination of the sample using the slovin method which resulted in 72 respondents. The results showed that there was a significant influence between Internal Marketing on customer decisions to choose iB Hijrah Savings by 68.9%, there is a significant influence between External Marketing on customer decisions to choose iB Hijrah Savings by 49.4%, there is a significant influence between Interactive Marketing on customer decisions to choose iB Hijrah Savings by 72.4%, and there is a significant influence between Internal Marketing, External Marketing, and Interactive Marketing simultaneously affect the customer's decision to choose iB Hijrah Savings at Bank Muamalat Indonesia KCP Rancaekek determination test of 80.3% while the remaining 19.7% is influenced by other variables not examined.